Time-motion analysis on Chinese male field hockey players - Liu, H.; Zhao, G.; Gomez, M. A.; Molinuevo, J. S.; Gimenez, J. V.; Kang, H. (International Journal of Performance Analysis in Sport, 2013)
The aim of the study was to evaluate the match work-rate of Chinese field hockey players by analyzing the distance covered at different intensities pooled by specific positions during different periods of matches. Thirty-eight players from twenty-four male field hockey matches at the 11th Chinese National Games were filmed and analyzed. Results showed that players covered an average distance of 7334±877m; 91.7% of this distance was covered at low and medium intensity; total distance covered in the first half (3693±441 m) was more (p<0.001) than the second (3640±437 m); distance covered at all speed zones (except walking) significantly decreased at the second half; total distance covered by forwards (7709±720 m) and midfielders(7733±729m) was greater than defenders (6671±745 m); positional difference were detected among all the speed zones as well; comparison of interaction of the match period and playing position showed higher values in sprinting during the first half compared to the second for forwards (p<0.01), and in moderate-speed running for defenders (p=0.0001). These results could be used to provide guidance on evaluating players' performance and formulating training prescriptions.